2004
DOI: 10.1093/jnci/djh135
|View full text |Cite
|
Sign up to set email alerts
|

Familial Clustering of Hodgkin Lymphoma and Multiple Sclerosis

Abstract: The observed familial clustering of multiple sclerosis and young-adult-onset Hodgkin lymphoma is consistent with the hypothesis that the two conditions share environmental and/or constitutional etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 23 publications
3
45
0
2
Order By: Relevance
“…on May 10, 2018. by guest www.bloodjournal.org From assessed among matched control subjects using the same hospital discharge registries, underdiagnosis of autoimmune and related disorders in subjects or their first-degree relatives should be nondifferential between patients and control subjects, and thus any bias should have been conservative, that is, toward a null association. 35,36 Another limitation is the large number of tested autoimmune and related conditions, which implies that one has to interpret detected associations with caution due to multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…on May 10, 2018. by guest www.bloodjournal.org From assessed among matched control subjects using the same hospital discharge registries, underdiagnosis of autoimmune and related disorders in subjects or their first-degree relatives should be nondifferential between patients and control subjects, and thus any bias should have been conservative, that is, toward a null association. 35,36 Another limitation is the large number of tested autoimmune and related conditions, which implies that one has to interpret detected associations with caution due to multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Ratios of the incidence of breast cancer in women with MS to that in women without MS served as measure of the relative risk (RR). Analyses were carried out using the proc GENMOD procedure in SAS, and adjustment was made for age (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) , . .…”
Section: Registersmentioning
confidence: 99%
“…As reported previously, we found no increased risk of haematopoietic and lymphatic cancers in the cohort. 17 Men with MS were at statistically significantly reduced risk of cancer overall (SIR 5 0.84 (0.76-0.93), n 5 361], reflecting low risk of cancers of the digestive and respiratory systems and the genital organs (Table I) (Table II). (Table III).…”
Section: Registersmentioning
confidence: 99%
See 1 more Smart Citation
“…EBV is associated with HL in 30–40% of cases [13,14,15], there are examples of familial clustering [16] and case reports of patients with both MS and HL [17,18,19,20] or MS with primary CNS lymphoma [21]. Such associations are disputed by Kurtzke and Hamtoft [22], who cite the disparate regional distribution of the two diseases in Denmark and the bimodal age of onset for HL but not MS. A record linkage study that used the Danish MS and Cancer Registries found no association between MS and HL [23].…”
Section: Discussionmentioning
confidence: 99%